Polygonatum tungnathensis (Asparagaceae), a new species from Uttarakhand, Western Himalaya, India - Singh, Ankit; Singh, Harsh; Nautiyal, Mohan Chandra (Phytotaxa, 2022)
A new species, Polygonatum tungnathensis is described and illustrated here from Uttarakhand Himalaya, India. This new species is similar to P. verticillatum, but it differs in its rhizome, leaves, inflorescence, pedicel length, perianth, fruits, seeds, and micro-morphological characters.